2017
DOI: 10.1016/j.scr.2017.02.006
|View full text |Cite
|
Sign up to set email alerts
|

Generation of an induced pluripotent stem cell line that mimics the disease phenotypes from a patient with Fanconi anemia by conditional complementation

Abstract: Generation of Fanconi anemia (FA) patient-specific induced pluripotent stem cells (iPSCs) has been reported to be technically challenging due to the defects in the FA-pathway in the patients' somatic cells. By inducible complementation of FA-pathway, we successfully reprogrammed the fibroblasts of an FA patient to iPSCs. CSCR19i-indCFANCA, one of the iPSC lines generated by the inducible complementation of FA-pathway, was extensively characterized for its pluripotency and karyotype. In the absence of doxycycli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 8 publications
0
6
0
Order By: Relevance
“…To overcome this challenge of generating isogenic wild-type and mutant iPSCs for recapitulating FA cellular phenotypes, we attempted base-editing to create mutations in the FANCA gene in AAVS1-iABE8e iPSCs. It has been reported earlier that iPSCs with FANCA homozygous mutations ( FANCA -/-) exhibit severe cell death, G 2 /M cell cycle phase arrest and loss of FANCD2 ubiquitination 50 – 52 . We performed ABE in the Dox-treated and untreated AAVS1-iABE8e iPSCs to create the FANCA L1082P mutation, which has been previously reported in some FA patients 53 (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…To overcome this challenge of generating isogenic wild-type and mutant iPSCs for recapitulating FA cellular phenotypes, we attempted base-editing to create mutations in the FANCA gene in AAVS1-iABE8e iPSCs. It has been reported earlier that iPSCs with FANCA homozygous mutations ( FANCA -/-) exhibit severe cell death, G 2 /M cell cycle phase arrest and loss of FANCD2 ubiquitination 50 – 52 . We performed ABE in the Dox-treated and untreated AAVS1-iABE8e iPSCs to create the FANCA L1082P mutation, which has been previously reported in some FA patients 53 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…6 A). Subsequently, we examined the FANCA homozygous mutant iPSCs for the previously described cellular phenotypes 50 – 52 .
Figure 6 Recapitulation of Fanconi anemia (FA) cellular phenotypes in FANCA base edited in AAVS1-iABE8e iPSCs.
…”
Section: Resultsmentioning
confidence: 99%
“…Inherited bone marrow failure syndromes (IBMFS) are another group of inherited blood disorders that are characterized by the decreased production of mature blood cells of one or more lineages, often with a predisposition to leukemia development. iPSC models of several IBMFS have been created, including Fanconi anemia (FA) (Bharathan et al, 2017; Chlon et al, 2014; Liu et al, 2014; Muller et al, 2012; Raya et al, 2009; Rio et al, 2014; Suzuki et al, 2015; Yung et al, 2013; Navarro et al, 2014), Shwachman Diamond syndrome (Tulpule et al, 2013), Diamond Blackfan anemia (DBA) (Doulatov et al, 2017; Garcon et al, 2013), dyskeratosis congenita (DC) (Agarwal et al, 2010; Batista et al, 2011; Gu et al, 2015; Jose et al, 2018), amegakaryocytic thrombocytopenia (Hirata et al, 2013) and severe congenital neutropenia (Morishima et al, 2014; Nayak et al, 2015; Pittermann et al, 2017; Hiramoto et al, 2013). Because IBMFS are characterized by a decline in the number and function of HSCs, iPSC-based cell therapy approaches, bypassing the need to harvest a patient's own HSCs, could hold promise for the future treatment of these diseases.…”
Section: Ipsc Models Of Hematologic Disordersmentioning
confidence: 99%
“…FA patients are susceptible to the development of various cancers. Efforts to reprogram somatic cells from FA patients revealed that FA cells are highly refractory to reprogramming (Bharathan et al, 2017; Chlon et al, 2014; Raya et al, 2009; Rio et al, 2014; Yung et al, 2013; Muller et al, 2012). This is perhaps the most dramatic example of a human disease-related pathway with such a profound effect on the reprogramming ability of the cells.…”
Section: Ipsc Models Of Hematologic Disordersmentioning
confidence: 99%
See 1 more Smart Citation